Comparison of Short-Term Effects of High-Intensity Interval Training vs Moderate Intensity Continuous Training on Anthropometric Characteristics of Overweight Young Women - Muhammad Sarfraz, Azadeh Shadmehr, Erum Naz, Mazhar Ali, Anila Rahim, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To conduct a comprehensive research work in order to find out the (time bound) efficient way to bring about changes in anthropometric measures with weight/fat reduction. Methods: In this study the effects of high intensity interval training (HIIT) and moderate intensity continuous training (MICT) were compared to see the reduction in body fat percentage in young university girls age between 20 to 25 years. Thirty subjects were recruited in HIIT (n=15) and MICT group (n=15) for 8 weeks. Pre and post fat percentage was assessed to see the changes before and after work out of two different exercise regimens. Results: Statistically significant improvement was found in both groups for weight (Mean difference = 3.04, P value = 0.00), However in the same manner other factors also showed significant improvement, BMI (Mean difference = 1.20, P value = 0.00), Waist circumference (Mean difference = 1.67, P value = 0.001), Hip circumference (Mean difference = 1.73, P value = 0.00) and body fat (Mean difference = 2.92, P value = 0.00). Therefore, all anthropometric measures showed differences but HIIT group showed maximum reduction in weight after regime (P value < 0.00) Conclusion: Eight weeks of HIIT and MICT resulted in improvements in anthropometric measures along with changes in dietary habit intake. HIIT appears to be the predominant strategy for controlling weight because of its adherence and time efficiency. Keywords: Overweight Young women, Moderate intensity continuous training , Weight reduction, Abbreviations: High intensity interval training (HIIT), Moderate intensity continuous training (MICT), Maximum Heart Rate (MHR), Body Mass index (BMI), Body Fat (BF)